Single-step fabrication of Mn(iv) oxide-Mn(ii) sulfide/poly-2-mercaptoaniline porous network nanocomposite for pseudo-supercapacitors and charge storage - Aldosari Eman; Rabia Mohamed; Zhang Qinfang; Altilasi Hissah Hamad (Open Physics)
The single-step fabrication of the Mn(iv) oxide-Mn(ii) sulfide/Poly-2-mercaptoaniline porous network nanocomposite (MnO2-MnS/P2MA) involves incorporating the Mn source into the P2MA polymer during polymerization. XPS analysis confirms the presence of peaks corresponding to Mn(iv) and Mn(ii), while XRD analysis highlights the formation of pronounced crystalline peaks, indicative of excellent semiconductive properties, with a crystalline size of 42 nm. The nanocomposite serves as the main electrode for electrochemically assessing its charge storage capabilities. Optimal energy density (E) values are achieved at lower current densities, with 9.7 and 7.0 W h/kg at 0.6 and 1.0 A/g, respectively. Similarly, the specific capacitance (C S) reaches peak values of 120 and 86 F/g within the same current density range. The electrochemical impedance spectroscopy (EIS) behavior is notable, with an R s value of 7.3 Ω and an impressive cycle retention of 99.2% over 1,000 cycles. The combination of simple one-pot fabrication, excellent charge storage performance, and high stability underscores the potential of these materials for charge storage applications. The MnO2-MnS/P2MA nanocomposite’s superior EIS behavior, optimal energy and capacitance values, and remarkable cycle stability make it a promising candidate for efficient and reliable charge storage solutions.